Homemade food, alcohol, and body weight: Change in eating habits in young individuals at the time of COVID-19 Lockdown - Elisa Mazza; Yvelise Ferro; Roberta Pujia; Samantha Maurotti; Tiziana Montalcini; Arturo Pujia (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The 2019 coronavirus disease (COVID-19) lockdown has caused significant changes in everyday life. This study evaluated the effect of the COVID-19 quarantine on dietary and alcohol consumption habits and body weight of Italian university students. MATERIALS AND METHODS: An online cross-sectional survey was carried out among university students than 18 years in July 2020. The online self-administered questionnaire included demographic and anthropometric data (reported weight and height), weight, and dietary habits changes during of the COVID-19 lockdown. RESULTS: A total of 520 respondents have been included in the study. A total of 393 (~76%) were female, 3.8% was obese, and the mean age was 23 ± 4 years. Numerous students reported a change in their eating habits during the lockdown with an increase in consumption of chocolate (40%), ice cream, and desserts (34%), but most of all an increase of homemade bread and pasta (60%), pizza (47%), and homemade sweets (55%). The students also reported an increase of vegetables, fresh fruit, legumes, eggs, and coffee, but also of processed meat, fried foods, cheeses, butter, and sweet beverage, and a reduction in alcohol intake. The weight gain was observed in 43.8%, and males have greater weight gain than females (57% vs. 46%, respectively; P = 0.04). A greater increase in body weight was observed in obese as compared to those with normal weight (77% vs. 44%, respectively; P < 0.001). CONCLUSIONS: Our data highlighted the need for dietary guidelines to prevent weight gain during the period of self-isolation, especially targeting those with overweight and obesity.